Use of Wheat Straw Ash as Cement Replacement Material in Concrete (International Journal of Innovative Research in Engineering & Management, 2022)
The impact of employing wheat straw  ash as a partial substitute material for cement in concrete  mining is presented in this research. Wheat straw ash is the  residue left over after open burning wheat straw. The  appropriateness of wheat straw ash obtained from  uncontrolled burning of wheat straw as a partial  replacement for cement in concrete is investigated in this  study. The compressive strength and workability of  concrete blended wheat straw ash cement are examined  and investigated by substituting cement by 15%, 20%,  25%, and 30% by weight to OPC. Slump tests were  performed on new concrete, and compressive strength tests  were performed on hardened concrete. Several cubes were  evaluated after 7 and 28 days. The results demonstrate that wheat straw ash is a decent  replacement material. The slump value dropped as wheat  straw ash increased. The compressive strength decreased  as WSA increased.
Keywords: Wheat Straw; Wheat Straw Ash; Slump Test; Sieve Analysis; Compressive Strength